The urban poor in Dhaka City: their struggles and coping strategies during the floods - Rashid, Sabina (BRAC Research and Evaluation Division (RED), 2020)
Poorer groups are exposed to increased vulnerabilities during periods of floods. Some of the difficulties faced by them include loss of possessions, fears of extortion and looting, and separation from their social network. The poor undertake different coping strategies to adapt to the floods such as abandoning land or housing, salvaging household items, selling land or livestock, and moving housing or family members to safer places. Perceptions of loss of the poor seem to be far more affected by damages in personal livelihood, and less by the overall scale of losses in the area. Women and children are often the most vulnerable groups during such disasters. Lack of sanitation facilities affected women badly. A majority of the latrines were submerged and inaccessible. This resulted in loss of privacy and shame for the women, with most being forced to defecate in their own homes. Some women were able to access, with great difficulty, latrines outside their neighbouring area. Floods usually result in an acute scarcity of safe drinking water clue to the contamination of water sources, such as tube-wells and reserve tanks. This adversely affects the existing poor health conditions of slum dwellers. There were numerous reports of diarrhoea and other illnesses amongst both children and adults. The floods left most of the urban poor unemployed. This resulted in an increase in tension and domestic violence, particularly towards women. In some areas, BRAC members were pressured into repaying loans even though most were severely affected by. the floods. Furthermore, NGOs chose to implement separate flood relief strategies instead of co-ordinating their efforts.